[Afisz. Incipit] Ogloszenie o rejestracji mezczyzn ur. w 1929 r. / J. Skarżyński. - Skarżyński, Jerzy Stanisław (1911-2003) ([wydawca nieznany], 1947)
Afisz informujący o rejestracji mężczyzn z rocznika 1929.